UTERINE SEROSAL INCLUSION CYSTS COUPLED WITH PYOMETRA IN A BITCH - SATHIAMOORTHY, T; RANGASAMY, S; ARUNMOZHI, N; BISWAL, S S; KULASEKAR, K (The Indian Journal of Animal Reproduction, 2023)
A case of uterine Serosal inclusion cyst coupled with pyometra and its successful management in a tenyear old German shepherd bitch was described in this report.
Keywords: CYSTS; PYOMETRA; BITCH